Does teleworking affect the labor income distribution? Empirical evidence from South American countries - Camusso, Jorge (2025)
This study aims to estimate the distributional impact of teleworking on the labor income in some South American countries, including Argentina, Brazil, Colombia, Ecuador, Peru and Uruguay. Using microdata from household surveys, our focus is on the period 2021 onwards to filter teleworking variables from temporary changes in the labor market caused by tighter restrictions on mobility during the pandemic. While in some countries we can measure effective teleworking, in others we approximate it based on a set of conditions that are standard in teleworking literature. Then, by using a RIF (Recentered Influence Function) regression approach, we estimate how a marginal variation in the percentage of teleworkers affects not only the mean of labor income, but also other features of unconditional distribution, such as quantiles and some inequality indicators (Gini and Atkinson indexes). This analysis allows us to capture potential asymmetric effects of remote work across the entire unconditional income distribution. The main results show that a marginal variation in the percentage of remote workers has a positive effect on the average labor income but with asymmetries across the income distribution that could lead to an increase in inequality. Indeed, for most countries, high-income workers benefit more from deeper teleworking penetration. Furthermore, this result is also supported by our estimates of the effect of teleworking on Gini and Atkinson inequality indexes.